Examining need for closure and need for cognition as predictors of foreign language anxiety and enjoyment. Issue 2 (7th February 2023) - Rezazadeh, Mohsen; Zarrinabadi, Nourollah
ABSTRACT: This study investigated the relationship between need for closure and need for cognition and foreign language anxiety and enjoyment. The participants of the study were 232 EFL learners at a university in Iran. Self-report questionnaires on need for closure, need for cognition, foreign language classroom anxiety and foreign language enjoyment were administered. The results of path analysis indicated that different aspects of need for closure and need for cognition predicted foreign language anxiety and enjoyment both directly and indirectly. The findings of the study highlight that the ways in which language learners' approach or avoid language knowledge and information play an important role in their emotions toward foreign language learning.